2005
DOI: 10.1097/01.aog.0000152350.10875.02
|View full text |Cite
|
Sign up to set email alerts
|

Dysplasia Associated With Atypical Glandular Cells on Cervical Cytology

Abstract: These data suggest that women with atypical glandular cells are at substantial risk for dysplasia and malignancy. The rate of disease varies with the method of Pap test collection, age, presence of persistent AGUS Pap tests, and AGUS subclassification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 21 publications
5
42
0
4
Order By: Relevance
“…In this study we tested 28 AGC liquid-based cytology for HPV DNA with posterior identification of 10 types of HPV DNA, 7 being high risk HPV DNA. The HPV associated disease ratio in our study was 50% which is in agreement with existing literature that reports rates which range from 11 to 53% (average 21%) [11].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we tested 28 AGC liquid-based cytology for HPV DNA with posterior identification of 10 types of HPV DNA, 7 being high risk HPV DNA. The HPV associated disease ratio in our study was 50% which is in agreement with existing literature that reports rates which range from 11 to 53% (average 21%) [11].…”
Section: Discussionsupporting
confidence: 93%
“…The association to premalignant and malignant disease is seen is approximately 30% of the cases [5,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…ACG are divided in two groups, according to their estimated significance: "possibly non-neoplastic" or "cannot exclude highgrade intraepithelial lesion", as the Nomenclatura Brasileira para Laudos de Colpocitologia (Brazilian Nomenclature for Cervical Cytology Reporting). The recommended approach, indeed, is the same, implying recommendation of immediate investigation through colposcopy with histological evaluation (5,13) .…”
Section: Introductionmentioning
confidence: 99%
“…The follow-up rate with histologic diagnosis can be as high as 94.5% [9], while other studies reported less than half this number [10]. Significant pathology diagnosed histologically on follow-up ranges from 9% [11] to over 60% [12] of cases. Reports comparing the performance of different preparations demonstrate inconsistent results on the prevalence of AGC, with some reporting higher rates on ThinPrep over conventional preparations [6, 13, 14] and others finding the opposite [15, 16].…”
Section: Discussionmentioning
confidence: 99%